2019
DOI: 10.5530/pj.2019.11.172
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacognostical and Preliminary Phytochemical Evaluation of Cordia sebestena L.

Abstract: Background: Cordia sebestena L. belongs to family Boraginaceae is commonly known as "Geiger Tree" in Indonesia, it is generally found in Indonesia included Jakarta, and many other countries. Some researchers have revealed the presence of several pharmacology activities. Thus this study is an attempt to present an overview of pharmacognostic and phytochemical evaluation reported on this plant. Objective: In the present investigation, various pharmacognostic standards have been investigated to prove the authenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…Phytochemical screening results in this study are following previous studies by Hanani et al 21 that ethanolic extract of C. sebestena leaves showed alkaloids, phenols, flavonoids, tannins, saponin, steroids, and terpenoids. It can be implied that the phytochemical compounds in C. sebestena leaves dissolved better in 70% ethanol solvent.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Phytochemical screening results in this study are following previous studies by Hanani et al 21 that ethanolic extract of C. sebestena leaves showed alkaloids, phenols, flavonoids, tannins, saponin, steroids, and terpenoids. It can be implied that the phytochemical compounds in C. sebestena leaves dissolved better in 70% ethanol solvent.…”
Section: Discussionsupporting
confidence: 88%
“…Meanwhile, EECS shows a high total ash value of 16.31%. Hanani et al 21 reported that ash values of powdered leaves of C. sebestena were found 13.6%. The amount and composition of ash remaining after the combustion of plant material vary considerably according to the part of the plant, treatment, age, location etc.…”
Section: Discussionmentioning
confidence: 99%
“…It may be due to their high polarity 13 . TLC profiling of crude extracts is crucial one for the development of quality parameters 20 . In this study, five pure compounds were isolated by TLC and two among them were characterized by spectral studies.…”
Section: -Petroleum Ether Extract; II -Chloroform Extract; Iii -Ethyl Acetate Extract; Iv -Methanol Extract; (+) -Positive Result; (++) -mentioning
confidence: 99%
“…Preparing for powder microscopic of the plants part were observed under the microscope and photographed. The procedure for the microscopic study was described in Indonesian Herb Pharmacopoeia 10 and Hanani et al 11…”
Section: Microscopic Studymentioning
confidence: 99%
“…Strong acids, alkalis and organic solvents were added and observed under the daylight and ultraviolet light at 254 nm and 366 nm. 11,15 Thin layer chromatography profile All fractions were analyzed for the chromatographic profile using TLC (silica gel 60 GF 254 ) with different solvents. Each fraction was solved with suitable solvents and spotted using the micro-pipette in the silica plate surface.…”
Section: Fluorescence Character Analysismentioning
confidence: 99%